Architect’s perception of factors contributing to construction project delay In planning & design phase: Case studies of private housing projects In Klang Valley, Malaysia / Ong Wee Yeak - Wee Yeak, Ong (2022)

(untitled)
For construction projects, a delay occurs when the project is unable to be finished on time. In Malaysia, delay is an unavoidable issue that occurs in all phases of construction project. Presently, the majority of past research has concentrated on determining the reasons of or resolving delays in the building phase; however, only a few studies have looked into delays in the planning and design phases. Thus, this study aims to to identify the factors that contributing to construction project delays in the planning and design phase, specially for the private housing projects. Quantitative research method is adopted as to meet the research objective. This research was conducted depend on the literature review and questionnaire survey. A questionnaire survey was conducted and delivered to respondents from architectural consultancy practice (ACP) registered with the Board of Architects Malaysia (LAM). Relative importance index (RII) analysis methods applied to justify the most critical delay factors for data analysis. Changes of client’s requirements was among the most critical causes of delay in the planning and design phases. The outcome of this research is good justification to propose some recommendations to mitigate delays for better performance of Malaysia’s private housing construction project.